Promoción del ahorro y ahorro previsional voluntario: Revisión de la literatura - Carlos Gustavo Machicado (Institute for Advanced Development Studies (INESAD), 2022)
– This document carries out an exhaustive review of the literature, at the microeconomic level, on mainly behavioral problems aimed at promoting voluntary savings for old age (retirement). The different mechanisms and/or tools described have been designed to promote this type of savings, especially among independent and low-income workers. Therefore, the results can be easily extrapolated to workers in the traditional agricultural sector, who are characterized precisely by being independent, with low and volatile incomes and by having a work structure - most of the time - family.
Keywords: E21; D14; J26; 330; Savings; household savings; retirement; literature review